Mobile Phone Text Messaging Intervention for Cervical Cancer Screening: Changes in Knowledge and Behavior Pre-Post Intervention - Lee, Hee Yun; Koopmeiners, Joseph S; Rhee, Taeho Greg; Raveis, Victoria H; Ahluwalia, Jasjit S (JMIR Publications, 2014)
BackgroundCervical cancer poses a significant threat to Korean American women, who are reported to have one of the highest cervical cancer mortality rates in the United States. Studies consistently report that Korean American women have the lowest Pap test screening rates across US ethnic groups. ObjectiveIn response to the need to enhance cervical cancer screening in this vulnerable population, we developed and tested a 7-day mobile phone text message-based cervical cancer Screening (mScreening) intervention designed to promote the receipt of Pap tests by young Korean American women. MethodsWe developed and assessed the acceptability and feasibility of a 1-week mScreening intervention to increase knowledge of cervical cancer screening, intent to receive screening, and the receipt of a Pap test. Fogg's Behavior Model was the conceptual framework that guided the development of the mScreening intervention. A series of focus groups were conducted to inform the development of the intervention. The messages were individually tailored for each participant and delivered to them for a 7-day period at each participant's preferred time. A quasi-experimental research design of 30 Korean American women aged 21 to 29 years was utilized with baseline, post (1 week after the completion of mScreening), and follow-up (3 months after the completion of mScreening) testing. ResultsFindings revealed a significant increase in participants' knowledge of cervical cancer (P<.001) and guidelines for cervical cancer screening (P=.006). A total of 23% (7/30) (95% CI 9.9-42.3) of the mScreening participants received a Pap test; 83% (25/30) of the participants expressed satisfaction with the intervention and 97% (29/30) reported that they would recommend the program to their friends, indicating excellent acceptability and feasibility of the intervention. ConclusionsThis study provides evidence of the effectiveness and feasibility of the mScreening intervention. Mobile technology is a promising tool to increase both knowledge and receipt of cervical cancer screening. Given the widespread usage of mobile phones among young adults, a mobile phone-based health intervention could be a low-cost and effective method of reaching populations with low cervical cancer screening rates, using individually tailored messages that cover broad content areas and overcome restrictions to place and time of delivery.